A study on Exploration of Consumer conformity factors: an Indian Perspective - Kaushal, Arun (International Journal of Psychosocial Rehabilitation, 2020)
Conformity is considered to be a major social psychology mechanism, and since last few decades its relevancy in constructive way is realized by the sociologists as well as psychologists. Consumer conformity is termed as alteration in the behavior of consumer when he /she got influential opinions from their referred group members. The alteration of behavior is the outcome of advice suggested by the group members. The main objective of the study is to determine the antecedents of the consumer conformity especially in Indian context. Primary data collection methodology used for sampling the population was non-probability sampling technique, in which this study used convenience sampling and snowball technique to choose the target audience. After considering the results of pilot study, few items were deleted as they seemed to be repetitive and 48 items being used for final scale. Finally for data analysis, exploratory factor analysis (EFA) has been used to explore the possible factors related to consumer conformity with the help of SPSS.20 version. Results of the study revealed that ATSCI (attention to social comparison information), collective self-esteem, list of values, and subjective norms and moral support of group members are the primary reasons due to which consumer seeks advice and suggestions from their peer group members for purchase related decisions.